A Behavioral Survey of the Effects of Kavalactones on Caenorhabditis elegans Neuromuscular Transmission. (13th April 2017) - Kautu, Bwarenaba B; Phillips, Juliana; Steele, Kellie; Mengarelli, M Shawn; Nord, Eric A
Kava is a plant root extract that is widely consumed by Pacific Islanders. Kava contains a class of lactone compounds called kavalactones. The sedative and anxiolytic effects of kava are likely attributed to the efficacies of kavalactones on the nervous system. Although some studies have implicated the potencies of certain kavalactone species on γ-aminobutyric acid transmission, evidence supporting the action of kavalactones on the eukaryotic neuromuscular junction (NMJ) and acetylcholine (ACh) transmission is scant. Here, we used behavioral assays to demonstrate the effects of kavalactones at the Caenorhabditis elegans NMJ. Our results suggest that kavalactones disrupt the inhibitory-excitatory balance at the NMJ. Such perturbation of NMJ activity is likely due to excess or prolonged ACh transmission. In addition, we found that kavain, a major constituent of kava, induced worm paralysis but not convulsions. Hence, the modulatory action of kavain could be distinct from the other kavalactone species.